EFEKTIVITAS PENYULUHAN GIZI SEIMBANG DENGAN MEDIA YOUTUBE DAN ZOOM TERHADAP PERUBAHAN PENGETAHUAN SISWA SMP AR RAFI'DRAJAT KOTA BANDUNG TAHUN 2022 - Salisa Tahany Jilan, (2022)
Good nutritional knowledge can influence food consumption to achieve good nutritional status. To increase the knowledge of nutrition in adolescents, it is necessary to conduct counseling about balanced nutrition. This study aims to determine the Effect of Balanced Nutrition Counseling with YouTube and Zoom Media on Knowledge Changes in Ar Rafi'Drajat Middle School Students, Bandung City. This study uses a quasi-experimental design carried out in April-May 2022 at Ar Rafi'Drajat Junior High School, Bandung City with a sample of 50 people. Data analysis used univariate analysis to describe the distribution and bivariate analysis used the Mann-Whitney test. Based on the results of the bivariate test, it can be seen that there is a difference in knowledge using YouTube media with the Asymp value. Sig. of 0.000 (Asymp. Sig. < 0.05). There is a difference in knowledge before and after providing education on Zoom media with the Asymp value. Sig. of 0.000 (Asymp. Sig. < 0.05). There is a difference in effectiveness between YouTube and Zoom media with the Asymp value. Sig. 0.002 (Asymp. Sig. < 0.05). YouTube media is more effective when compared to Zoom media.